Influence of Mn and Cr impurities on quasi-surface exciton states of BiI₃ layered single crystals - Dorogan, V.G.; Zhydkov, V.O.; Motsnyi, F.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The influence of Mn and Cr impurities on quasi-surface excitons of BiI3 single crystals was studied. The broadening of their band was found which may be caused by ionization of quasi-surface excitons by the electric field of Mn²+ and Cr³+ ions.